Real-space imaging of anisotropic charge of σ-hole by means of Kelvin probe force microscopy - Mallada, B; Gallardo, A; Lamanec, M; de la Torre, B; Špirko, V; Hobza, P; Jelinek, P (Science (New York, N.Y.), 2021)
An anisotropic charge distribution on individual atoms, such as σ-holes, may strongly affect the material and structural properties of systems. However, the spatial resolution of such anisotropic charge distributions on an atom represents a long-standing experimental challenge. In particular, the existence of the σ-hole on halogen atoms has been demonstrated only indirectly through the determination of the crystal structures of organic molecules containing halogens or with theoretical calculations, consequently calling for its direct experimental visualization. We show that Kelvin probe force microscopy with a properly functionalized probe can image the anisotropic charge of the σ-hole and the quadrupolar charge of a carbon monoxide molecule. This opens a new way to characterize biological and chemical systems in which anisotropic atomic charges play a decisive role.